Răspuns :
Explicație pas cu pas:
a+b+c=540
a=3b
c=a-b
a+b+c=a+b+(a-b)=a+b+a-b=2a=540
2a=540 /:2
a=270
a=3b => b=a/3=270/3=90
c=a-b=270-90=180
a=primul termen
b= al doilea termen
c= al treilea termen
Suma: a+b+c=540
a=3b
c=a-b
Din datele problemei inlocuim pe c cu a-b in suma, si rezulta:
a+b+a-b=540
2a=540
a=270
3b=a
3b=270
b=270:3
b=90
c=a-b
c=270-90
c=180
R: (a=270;b=90;c=180)
b= al doilea termen
c= al treilea termen
Suma: a+b+c=540
a=3b
c=a-b
Din datele problemei inlocuim pe c cu a-b in suma, si rezulta:
a+b+a-b=540
2a=540
a=270
3b=a
3b=270
b=270:3
b=90
c=a-b
c=270-90
c=180
R: (a=270;b=90;c=180)